The Effect of Rice Price, Income Per Capita, Population on Rice Demand in Sulawesi Island using Panel Data Regression - Irwandi, Irwandi; Rahim, Abd.; Rahmasari, Astrid; Aulia, A. Rizqa Nurul; Nurmi, Nurmi; Rusman, Aldha (Bina Bangsa International Journal of Business and Management, 2023)
Panel data regression analysis is a combination of cross section data and time series data. This study aims to analyze how the effect of rice prices, per capita income, population on the demand for rice on the island of Sulawesi. Using a combination of cross-sectional data, namely the six provinces on the island of Sulawesi and time series data from the 2017-2020 period. The results of the research show that the population and income per capita have a significant influence on the demand for rice on the island of Sulawesi. Meanwhile, the price of rice has no significant effect on the demand for rice on the island of Sulawesi. From the R2 value, it is 95.1453%, which means the variance of rice prices, population, and per capita income to the demand for rice on Sulawesi Island, while the rest is influenced by other variables not included in the model